Novel 11-Substituted Ellipticines as Potent Anticancer Agents with Divergent Activity against Cancer Cells - Charlotte M. Miller (Pharmaceuticals, 2019)
Ellipticines have well documented anticancer activity, in particular with substitution at the 1-, 2-, 6- and 9-positions. However, due to limitations in synthesis and coherent screening methodology the full SAR profile of this anticancer class has not yet been achieved. In order to address this shortfall, we have set out to explore the anticancer activity of this potent natural product by substitution. We currently describe the synthesis of novel 11-substituted ellipticines with two specific derivatives showing potency and diverging cellular growth effects.